Koagulyant-adsorbenttiń adsorbciyalıq qásiyetin kolorimetriyalıq usıl menen úyreniw - Aymurzaeva, L.G; Aytbaeva, H.B; Qutlimuratova, Sh.A (ILIM hám JÁMIYET, 2025)
This article presents the adsorption properties of thermally activated coagulants-adsorbents, the structural- sorption indicators of coagulants-adsorbents, and the pore volume, as well as their dependence on adsorption.